Effect of intraductal drug delivery of orexin receptor antagonists into lactating rat mammary gland on milk cholesterol metabolism by regulating Fas and Hmgcr genes - Zandieh, Shima Jafari; Khazali, Homayoun (Acta Biologica Szegediensis, 2023)
In recent years, many studies have demonstrated that the system of orexin plays a pivotal role in regulating lipogenesis enzymes. However, its effect on the mammary glands is not entirely known. This study answers the question of whether intra-ductal injection of orexin antagonists (OX1RA and OX2RA) into the mammary glands can result in the expression of fatty acid synthase (Fas) and HMG-CoA reductase (Hmgcr) genes and the secretion of cholesterol in lactating female rats or not. To this end, 42 Lactating rats were randomly divided into experimental groups including a control group and groups receiving OX1RA and OX2RA intraductal (with doses of 5, 10, and 20 µg/kg, i.duc). Milk samples were collected for cholesterol testing. Using specific primers for each gene, the target genes were measured via real-time PCR. Data differences were considered significant with P <0.05. PCR exhibited that the injection of orexin antagonists significantly reduced Fas and Hmgcr gene expression. Moreover, the injection of antagonists significantly reduced milk cholesterol. Intra-mammary injection of orexin antagonists reduces milk cholesterol levels by affecting the expression of Fas and Hmgcr genes.